Rencana Strategis Bagian Pemerintahan Kabupaten Solok dalam Meningkatkan Efektivitas dan Efisiensi Tata Kelola Pemerintahan Daerah - Fajri Afrizal; Syafwandi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study develops the strategic plan for the government section of Solok to enhance the effectiveness and efficiency of regional government administration. The method employed is qualitative research based on literature review and analysis of official documents related to strategic planning and governmental governance. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats faced by the governance section of Solok Regency. The findings highlight the importance of strengthening human resource capacity, refining work procedures, integrating information technology, and improving coordination among units and stakeholders as main strategic steps. The formulated strategic plan includes vision, mission, goals, targets, as well as priority programs and activities that support sustainable regional development. The recommendations aim to serve as a foundation for improving performance and governance of Solok Regency government in coping with the dynamics of governance and increasing demands for public service.